Evaluasi Implementasi Komponen Smart City di Bali : Literature Review - Lintang Pramudya; Ngurah Indra ER (Majalah Ilmiah Teknologi Elektro, 2025)
A smart city is a concept that integrates information and communication technology to improve the efficiency of public services, the quality of life of citizens and environmental sustainability. Bali, as one of the largest tourism centers in Indonesia, has started implementing the smart city concept to support economic development and overcome the challenges of urbanization. This research aims to evaluate the implementation of smart cities in Bali through a literature review approach, focusing on six main components of smart cities. Analysis was carried out on various national and international studies and reports related to smart city implementation in Bali, especially in the Denpasar and Badung areas to identify the stages of development and implementation of each component. The main focus is to examine how technology has been applied in the public service, transportation, security and tourism sectors, as well as the challenges faced in implementing this technology. The evaluation results show that the implementation of the smart city concept in Bali still faces several challenges, including limited technological infrastructure and low community digital literacy. This research provides recommendations for increasing the effectiveness and maturity of smart city implementation in the future. It is hoped that the results of this research can become a reference for the government and stakeholders in planning a more integrated and sustainable smart city development strategy in Bali.